The effectiveness of far-infrared irradiation on foot skin surface temperature and heart rate variability in healthy adults over 50 years of age: A randomized study. Issue 50 (11th December 2020) - Peng, Tai-Chu; Chang, Su-Ping; Chi, Lee-Mei; Lin, Li-Mei
Abstract: Background: Far-infrared irradiation (FIR) is used in the medical field to improve wound healing, hemodialysis with peripheral artery occlusive disease, and osteoarthritis but seldom used in ameliorating poor lower extremity circulation. The purpose of this study was to evaluate the effect of FIR on changes in foot skin surface temperature (FSST) and autonomic nerve system (ANS) activity to evaluate its effectiveness in improving lower limb circulation. Methods: A randomized controlled study was conducted. Subjects (n = 44), all over the age of 50 years and satisfying the inclusion criteria, were randomly allocated into 2 groups. The intervention group received FIR on a lower limb for 40 minutes and the control group received no intervention. Left big toe (LBT), right big toe (RBT), left foot dorsal (LFD), right foot dorsal (RFD) surface skin temperature, autonomic nervous activity, and blood pressure were assessed. Results: The main results were skin surface temperature at the LBT increased from 30.8 ± 0.4°C to 34.8 ± 0.4°C, at RBT increased from 29.6 ± 0.4°C to 35.3 ± 0.4°C and LFD increased from 31.9 ± 0.3°C to 36.4 ± 0.4°C, RFD increased from 30.7 ± 0.3°C to 37.7 ± 0.2°C. FIR caused a significant increase of the FSST ranging in a 4°C to 7°C increase after 40 minutes irradiation ( P < .001). The ANS low-frequency (LF) and high-frequency (HF) activity showed a statistically significant increase in the FIR group ( P < .05) but not the LF/HF ratio. Conclusion: FIR significantly increased the FSST from between 4°C and 7°C after 40 minutes irradiation, which might improve lower extremity circulation and regulation of ANS activity.